Assessing the contribution of the capital markets on the economic growth of Botswana - Radikoko, Ishmael (Archives of Business Research, 2019)
This study is conducted to evaluates the contribution of capital markets on the economic growth of Botswana. It focuses on the bond markets and stock markets using the Botswana Bond Index and the Domestic Companies Index as proxies respectively, and Gross Domestic Product as a measure of economic growth. A 6 year quarterly time series data from 2012 to 2017 was used in the analysis. Multiple regressions model was employed followed by cointegration test to establish the significance and long-run relationship respectively between capital markets and economic growth. Vector Error Correction Model is also employed to check for short term dependencies in the data series used. The findings from this research suggest that capital markets in Botswana do not contribute to economic growth in the short run. However, in the long run capital markets do contribute to economic growth through further capital markets development. The implications are that in the short run government and policy makers should devise appropriate policies that will improve the development of capital markets as thus have a potential to foster economic growth in the long run.